PERBANDINGAN PROFIL SEL DARAH PADA PASIEN DEMAM DENGUE DAN DEMAM TIFOID DI PUSKESMAS KOTA TASIKMALAYA: Comparison of Blood Cell Profiles in Dengue Fever and Typhoid Fever at Public Health Centers in Tasikmalaya City - Dina Ferdiani; Meri Meri (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2024)
Dengue fever and typhoid fever are infectious diseases frequently found in tropical regions and may present with similar early symptoms, especially fever. Routine hematology examination can support clinical consideration by showing differences in blood cell profiles. This study aimed to compare leukocyte, platelet, and erythrocyte profiles in patients with dengue fever and typhoid fever at public health centers in Tasikmalaya City. This descriptive comparative study used primary data from 30 febrile patients: 15 rapid dengue-positive patients and 15 rapid typhoid-positive patients. Leukocyte, platelet, and erythrocyte counts were examined manually using a counting chamber, and data were analyzed descriptively and comparatively. The mean platelet count was markedly lower in dengue patients than in typhoid patients (103.0 x 10^3/uL vs. 277.1 x 10^3/uL; p<0.001). All dengue patients showed thrombocytopenia, whereas most typhoid patients had platelet counts within the reference category. The mean leukocyte count was relatively similar between typhoid and dengue groups (5,853/uL vs. 5,767/uL; p=0.921), although leukopenia was observed in both groups. The mean erythrocyte count was also similar between typhoid and dengue groups (4.97 x 10^6/uL vs. 4.86 x 10^6/uL; p=0.649). In conclusion, platelet count was the most distinctive hematological parameter between dengue fever and typhoid fever in this study, while leukocyte and erythrocyte counts showed relatively similar averages.